Use of Pesticides and Health Risk among Farmers in Sunsari District, Nepal - Lamichhane, Rajendra; Lama, Nishant; Subedi, Sangam; Singh, Suman Bahadur; Sah, Ram Bilakshan; Yadav, Birendra Kumar (Journal of Nepal Health Research Council, 2019)
Background: An increasing widespread use of Pesticides is as an issue in the agricultural sector. Pesticides use is one of the occupational risks in farmers of low-income countries including Nepal. Objective of this study was to explore the health effects of Pesticides among agricultural farmers of Sunsari.Methods: A community based cross sectional study was carried out in Duhabi-Bhaluwa of Sunsari District, Nepal from September 2015 to February 2016. Non-probability sampling technique was used to enroll the total 300 study participants. Data were collected by face to face interview with farmers using pre-tested semi structured questionnaire. Data were recorded by reading the original container of the Pesticides.Results: Fungicides (60.3%), Herbicides (56.3%), pyrethrum (35.3%) and Organophophate (11.6%) Pesticides were commonly used by the agricultural farmers in their farms. The health problem within 48 hours after application of pesticides was reported by more than one-sixth (17%) of the farmers. Dizziness (74.5%) and headache (58.8%) were the most common health problems found among the farmers. Skin irritation (19.6%), nausea (13.7%), paraesthesia (9.8%), restlessness (5.8%), eye irritation (5.8%) and vomiting (1.9%) were also reported by pesticides handlers. Factors associated with health problems were hazardous pesticides use (AOR=26.95, CI 6.15 - 118.0), good knowledge on impacts of pesticides (AOR=3.16, CI 1.09-9.13), determination of wind direction first and spray (AOR=2.25, CI 1.08-4.67), working experience of 20-29 years on farm (AOR=3.38, CI 1.05-10.83). Conclusions: One-sixth of the farmers reported health problems. Farmers working with hazardous Pesticides were in need of special attention in terms of safe handling, determing the wind direction and spray.Keywords: Farmer; health hazardious; health risk; pesticides use.